2021
DOI: 10.3389/fmicb.2021.647611
|View full text |Cite
|
Sign up to set email alerts
|

In vitro Antibacterial Activity of an FDA-Approved H+-ATPase Inhibitor, Bedaquiline, Against Streptococcus mutans in Acidic Milieus

Abstract: BackgroundDental caries is an acid-related disease. Current anti-caries agents mainly focus on the bacteriostatic effect in a neutral environment and do not target acid-resistant microorganisms related to caries in acidic milieus.ObjectivesTo assess the in vitro antibacterial activities of bedaquiline against oral pathogens in acidic milieus.MethodsStreptococcus mutans, Streptococcus sanguinis, and Streptococcus salivarius were used to prepare the mono-/multiple suspension and biofilm. The MIC and IC50 of beda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…25 μg ml –1 bedaquiline) reduced the growth rate of the bacteria to half that of the control ( p < 0.001). Our pervious study had found that at pH 7, bedaquiline cannot inhibit the biofilm formation of S. mutans ( Zhang et al, 2021 ). In order to figure out the reasons for these inconsistent results, we had conducted additional study to measure the pH change of medium during bacterial growth.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…25 μg ml –1 bedaquiline) reduced the growth rate of the bacteria to half that of the control ( p < 0.001). Our pervious study had found that at pH 7, bedaquiline cannot inhibit the biofilm formation of S. mutans ( Zhang et al, 2021 ). In order to figure out the reasons for these inconsistent results, we had conducted additional study to measure the pH change of medium during bacterial growth.…”
Section: Resultsmentioning
confidence: 99%
“…The stable and cohesive biofilm formed by S. mutans ( Cross et al, 2006 ; Koo et al, 2013 ) can block the penetration of antibacterial agents, including bedaquiline ( Zhang et al, 2021 ). This is a key self-protection property of biofilms.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations